Using protein/creatinine ratios in random urine - Watanabe, Mitsuhiro (J Clin Lab Anal, 2005)
We assessed the new test paper Multistix PRO IOLS, in which the ±region of the conventional test for protein was altered so that creatinine correction became possible. Urinary samples from 235 patients with various renal diseases were obtained from the Juntendo University Hospital. We examined 1) the correlation between qualitatively measured values of urinary protein by the new test paper and the conventional test paper, and 2) the correlation between qualitative and quantitative values of protein (P), creatinine (C), and the P/C ratio measured by the new test paper. There was a good correlation between the P/C ratio observed with the new test paper and that observed by quantitative analysis. There was also a good correlation of the P/C ratio between 24‐hr urine and urinary samples obtained at any time of day. Thus, it appears that the results obtained from urinary samples any time of day can predict the amount of protein excreted during the day. J. Clin. Lab. Anal. 19:160–166, 2005. © 2005 Wiley‐Liss, Inc.